Effect of mobile-based self-management application on stroke outcomes: a study protocol for triple blinded randomized controlled trial. - Tadayon, Hamidreza; Farzandipour, Mehrdad; Nabovati, Ehsan; Akbari, Hossein; Masoud, Seyed Ali (BMC Medical Informatics & Decision Making)
Background: Stroke is the main leading cause of long-term disabilities in the world. This protocol will be implemented for a study to evaluate the effects of an Android-based self-care application on patients with stroke.Methods: The first stage will include the development of an android-based application using JAVA programming language for developing the user interface and ASP.NET Core for developing Web server. The second stage will be conducted using triple blinded randomized clinical trial (RCT). The sample size will include 60 patients with recent stroke and partial paralysis of limbs, who will be divided into two groups of intervention and control through permuted block randomization method. Patients in both groups will receive usual medical care, but those in the intervention group will also use an Android-based application for a period of two months. Outcomes will be assessed using valid and reliable questionnaires.Discussion: The assessed outcomes will include stroke severity using National Institute of Health Stroke Scale (NIHSS) score, ability to perform activities of daily living using Barthel Index (BI) score, depression rate using Beck Depression Inventory (BDI-II) score, quality of life using EQ-5D-3L score, medication adherence using Modified Morisky Medication Adherence Scale (MMAS-8) score, patient satisfaction using Patient Satisfaction Questionnaire (PSQ) score and the number and type of complications in patients in two groups. These outcomes will be assessed at baseline, after two months and after three months from the beginning of the intervention. Intervention effects on the measured variables will also be evaluated using appropriate statistical tests based on the type of variable distribution. Potential consequences of the study might be the improvement of the measured variables in the intervention group compared to that of the control group. The expected results are that the intervention may significantly improve the status of the measured variables in the intervention group compared to that of the control group. If the outcomes of the intervention group do not change significantly compared to those of the control group, it can be due to different reasons. However, this can most likely be attributed to incorrect or insufficient use of the application by patients.Trial Registration: This protocol is registered in the Iranian registration of clinical trial (IRCT) on November 7, 2020 with the code IRCT20201015049037N1. URL: https://irct.ir/trial/51674.